2020
DOI: 10.1148/radiol.2020190919
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Microwave Ablation versus Laparoscopic Partial Nephrectomy for cT1a Renal Cell Carcinoma: A Propensity-matched Cohort Study of 1955 Patients

Abstract: VASCULAR AND INTERVENTIONAL RADIOLOGYR enal cell carcinoma (RCC) is a heterogeneous group of kidney cancers mostly of proximal tubule origin (1) and represents more than 90% of all kidney cancers (2). The global yearly incidence of RCC is estimated at six per 100 000 men and three per 100 000 women (3). Patients with T1a RCC are considered to have a good prognosis, with a frequency of distant metastasis of 0.7%-7.2% (4).Current treatment guidelines recommend partial nephrectomy as the preferred treatment for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 33 publications
(32 reference statements)
4
39
1
1
Order By: Relevance
“…In this setting, the need of multiple treatments is generally accepted and taken into account during multidisciplinary discussions when establishing the patient treatment strategy. In fact, with a second ablation complete tumor ablation can be achieved in the large majority of cases [30,31,34]. Furthermore, patients can have a local tumor progression during follow-up, develop new foci of renal tumors in the same or in the contralateral kidney, or distant metastases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this setting, the need of multiple treatments is generally accepted and taken into account during multidisciplinary discussions when establishing the patient treatment strategy. In fact, with a second ablation complete tumor ablation can be achieved in the large majority of cases [30,31,34]. Furthermore, patients can have a local tumor progression during follow-up, develop new foci of renal tumors in the same or in the contralateral kidney, or distant metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, patients can have a local tumor progression during follow-up, develop new foci of renal tumors in the same or in the contralateral kidney, or distant metastases. In all these scenarios, image-guided thermal ablation can be applied to achieve disease control [30,[33][34][35][36]. Thus, it might easily occur that a patient requires multiple ablations over the course of his disease.…”
Section: Discussionmentioning
confidence: 99%
“…Besides nephrectomy, an alternative treatment approach for patients with small, incidentally detected RCC is radiofrequency ablation or cryoablation. 17,18 Ablation may be considered for selected patients with masses <4 cm who are poor surgical candidates or who require nephron-sparing treatment of their masses. While ablation was discussed preoperatively with our patients, the decision was made to proceed with resection as both diagnosis and treatment of the lesion, while minimizing the need for long-term surveillance, and given the limited role for preserving native renal function in the setting of ESRD.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of major complications, a 1.8% of meta-analytic pooled incidence was found (15). Study with the largest number of patients is reported in the single-center retrospective series from Liang et al in China ( [59], LoE 4). The authors included 185 patients with 192 sporadic T1a RCCs that were treated with US-guided percutaneous MWA.…”
Section: Effectivenessmentioning
confidence: 99%
“…The largest sample report on CT-guided percutaneous MWA of RCC is from Wells et al in USA ( [51], LoE 4), which showed the LTP rate was 1% (1/100) and 3-year OS was 91%. By now four reports have compared surgery and MWA in RCC patients with comparative oncologic survival outcomes ( [27,42,59,60], LoE 3). In addition, MWA has also been compared with cryoablation and RFA in treating small RCC from case control study.…”
Section: Effectivenessmentioning
confidence: 99%